Leadership Performance and Public Service Quality in Family Planning Services: Evidence from Local Government in Indonesia - Ade Setiadi (Sultan Publisher, 2023)
The performance of leadership is important in determining the quality of public services, especially around family planning programs that require good coordination and delivery of services oriented to citizens. Yet, empirical evidence on how leadership performance contributes to the quality of public services at the local government level is still limited. This study aims to examine the effect of leadership performance on public service quality in family planning services at the Regional Technical Implementation Unit for Population Control, Family Planning, Women's Empowerment, and Child Protection in Bongas District, Indramayu Regency, Indonesia. A quantitative explanatory approach was applied, with a survey of 85 respondents who were service users. Data were collected using structured questionnaires and analyzed using descriptive statistics, validity and reliability tests and path analysis. The results of the description indicated that the performance of leadership was perceived as good with a mean score of 3.77 in total. The quality of public service also achieved a good category with a mean score of 3.95 in total. The results of hypothesis testing show that leadership performance has a positive and significant effect on the quality of public services (F = 85.412, p < 0.001). The contribution of leadership performance to the quality of public services is 94.7% (R2 = 0.947). The results show that improving the leadership capabilities in work planning, implementation, work quality and target accomplishment can significantly improve the quality of public services. The study provides empirical evidence to justify leadership development as a strategic strategy for improving the effectiveness of family planning services in local government institutions.